Practical Fight )Qit’al( against Terrorism & Violence of The Holy Prophet (PBUH): A Research Study : - Muhammad Tahir Akbar (BNBWU Journal of Multidisciplinary Research, 2025)
Hazrat Muhammad(PBUH) established the Khilafat of Allah without any large army, bloodshed and killings. He made an educated and civilized nation of history and adopted many methods. In this study, an attempt has been made to explain 29 methods out of these many methods of practical jihad and fighting in simple words. Our Holy prophet ( S.A.W.W) also created a wide network of intelligence and undercover activities for the establishment of peace and from time to time many small units were sent under this system of espionage. It is the miracle Muhammad ﷺ that on the occasion of the conquest of Makkah, in one night without a fight, the entire city which was his mortal enemy became the one who sacrificed his life for him. The establishment of the Divine Caliphate on 3 million square kilometers without bloodshed is the only characteristic of him, in which only 250 martyrdoms took place. However during the same period, millions of people were killed in the few-day wars of Caesar and Kasra.